Inclusive language regarding gender, sexual orientation, and relationship status: the ongoing process and outcome of revising psychiatric materials. Issue 6 (11th October 2019) - Drill, Rebecca; Malone, Johanna; Flouton-Barnes, Meredith; Cotton, Laura; Keyes, Sarah; Wasserman, Rachel; Wilson, Kelly; Young, Monica; Laws, Holly; Beinashowitz, Jack
Abstract : Purpose: The purpose of this paper is to address the barrier to care experienced by LGBTQIA+ populations by binary language for gender, sexual orientation and relationship status. Design/methodology/approach: The authors review the research that shows linguistic barriers are a significant obstacle to healthcare for LGBTQIA+ communities. The authors describe both a process and revisions for addressing language bias in psychiatric intake/research research materials as well as quantify its impact in an adult psychotherapy clinic in a public hospital. Findings: Patients self-identified their gender, sexual orientation and relationship status in a variety of ways when not presented with binaries and/or pre-established response choices. In addition, the non-response rate to questions decreased and the authors received positive qualitative feedback. The authors also present the revisions to the intake/research materials. Practical implications: Other healthcare settings/clinicians can revise language in order to remove significant barriers to treatment and in doing so, be welcoming, non-pathologizing and empowering for LGBTQIA+ consumers of mental health services (as well as for non-LGBTQIA+ consumers who are in non-traditional relationships). Social implications: This work is one step in improving healthcare and the healthcare experience for LGBTQIA+ communities and for those in non-traditional relationships. Originality/value: This work is set in a public safety-net hospital providing care for underserved and diverse populations. This paper describes the process of revising psychiatric materials to be more inclusive of the range of self-identity are: gender, sexual orientation and relationship status.